1995
DOI: 10.1099/13500872-141-7-1609
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of the outermost capsular material of the tubercle bacillus

Abstract: To gain insight into the pathogenesis of tuberculosis, a molecular definition of the tubercle bacillus cell envelope, which is involved in the early stages of the infection, is required. The cell-surface-exposed material of the pathogen was isolated by mechanical means and chemically analysed. It was shown by scanning electron microscopy that the method used for extracting the surfacecovering material preserves the integrity of the bacilli. Surprisingly, in view of the current opinion, only small amounts of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
255
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(277 citation statements)
references
References 38 publications
21
255
0
1
Order By: Relevance
“…20). Some of these biologically active molecules have been precisely localized in the outermost layer of the cell envelope (15,21), but the precise location of others is still a matter of debate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20). Some of these biologically active molecules have been precisely localized in the outermost layer of the cell envelope (15,21), but the precise location of others is still a matter of debate.…”
mentioning
confidence: 99%
“…We extracted mycobacterial surface-exposed compounds by gentle surface abrasion with glass beads (15) and tested their role in the interactions between mycobacteria and MDMs to identify the most active bacterial partners of the phagocytic process. Because we have demonstrated that pathogenic and nonpathogenic strains use the same phagocytic receptors to infect cells (9,10,22,23), this work was performed with the nonpathogenic species, M. smegmatis.…”
mentioning
confidence: 99%
“…In mycobacteria, a polysaccharide-protein capsule [13] surrounds the peptidoglycan/arabinogalactan/mycolic acid cell wall [30]. Mycolic acids and free lipids are thought to contribute to the unusually low permeability of the mycobacterial cell wall which is believed to play a role in the resistance of mycobacteria to therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The smooth glass beads treatment, releasing mainly the capsular material [13], contained between 5 and 10% of the total enzyme activity found in the soluble extract prepared after complete disruption of the cells. The steel beads preparation, containing components more deeply embedded in the cell envelope, presented about 20% of the total enzyme activity.…”
Section: Cellular Localization Of the Adh Enzymementioning
confidence: 99%
See 1 more Smart Citation